Health risks associated with dietary supplements for athletes - Mariusz Zapadka; Dorota Rutkowska; Ewa Obońska; Bogumiła Kupcewicz (Polish Pharmaceutical Society, 2021)
A properly designed and balanced diet is an essential element of any training plan. Breaking down barriers and overcoming the limits of human endurance are at the heart of sports activity. Ever since high-performance sports, people have tried to gain an advantage over the competitor, i.e., by consuming various substances. The pursuit of being more agile, faster, stronger, and more enduring has given rise to a multi-billion dollar dietary supplements market. Athletes' dietary supplements can be divided into sports food, vitamin and minerals, and ergogenic supplements. Despite the centuries-old history of doping, the problem of substances that improve performance is still the most discussed topic in modern all types of sport, regardless of discipline or popularity. Dietary supplements are considered safe products, but their concentrated form may expose consumers to the risk of overdosing. Sports supplements are dangerous because they often have higher doses of substances than over-the-counter medicinal products. Taking many dietary supplements, often with prescribed medications, increases your risk of harmful interactions. Another problem related to dietary supplements is the lack of uniform legal regulations, and hence the high probability of adulteration with substances prohibited in sport or substances hazardous to health. During the COVID-19 pandemic and over the isolation, the number of people exercising at home increased. In problematic contact with primary health care, social media became the main information source about athletes' dietary supplements, their effectiveness, and safety. Not only nutritionists but also pharmacists and doctors should participate in assessing athletes' needs and health problems. The increase in health awareness and knowledge about dietary supplements for athletes should be permanently included in the map of health services of the integrated health care model. The decision to take a dietary supplement should be consulted as part of pharmaceutical care or a visit to the doctor. On the other hand, the selection of a specific preparation should be made based on certified brands that verify, authenticate labels, test for the presence of contaminants and substances prohibited in sports. In healthcare, system solutions are needed that focus on strict control and official certification of dietary supplements, as is the case in the pharmaceutical industry. Creating a state certification system for dietary supplements seems essential as a reliable source of verified information for medical professionals.